Public Satisfaction Survey On Registration Services Of Hindu Religion Education Institutions In Bali Province - Ni Komang Sutriyanti; I Made Dharmawan (Jayapangus Press, 2022)
The Regulation issuance of the Religion Minister of the Republic Indonesia No. 56/2014 that concerning on Hindu Religion Education in formal and non-formal education forms requires the Directorate General of Hindu Community Guidance to organize a registration service. The quality of the registration service needs to be surveyed as an evaluation of the implementation of public services. The subjects in this survey research are leaders / managers of formal and non-formal pasraman in Bali who already have registration list in 2020. The aspects that reviewed to determine service satisfaction are based on 14 minimum elements as indicators that must exist as a basis for measuring IKM on public service performance that are in accordance to the Ministerial Decree No. PAN. 25 of 2004. The sampling technique was carried out using disproportionate stratified random sampling, the data collection technique used an attitude scale as the main data and interviews and document studies as supporting data. Data were analyzed descriptively which were the community satisfaction score was sought first, the score was then adjusted to the criteria table. Overall, the level of community satisfaction with registration service of Hindu religious education institutions was very high. This can be proven by the average community satisfaction score of 82.75 (very high). In addition, if it was reviewed based on aspects of public service, among the 14 (fourteen) aspects of service, there were 4 (four) aspects that got very high satisfaction, namely discipline of officers, fairness of service, courtesy of officers and environmental comfort, while other aspects were in high satisfaction criteria. If it was reviewed by regency / city, all districts / cities in the Bali province got satisfaction score with very high criteria. Factors that affected public satisfaction with the sign service of Hindu religion education institutions include planning, leadership, monitoring of reliability, responsiveness, assurance, empathy, tangible, and tangible factors, certainty and service costs.